Evaluation and Validation of Real-Time Reverse Transcription-PCR Assay Using the LightCycler System for Detection and Quantitation of Norovirus - Pang, Xiaoli (American Society for Microbiology, 2004)
We developed an assay for the detection and quantitation of norovirus with the LightCycler SYBR Green-based real-time reverse transcription-PCR (real-time LC RT-PCR) and previously published primers in the capsid and the polymerase gene. One hundred thirty-two stool specimens from the Provincial Laboratory for Public Health (Microbiology), Alberta, Canada, and the Centers for Disease Control and Prevention, Atlanta, Ga., were used to validate the new assay. The samples were collected from patients involved in outbreaks of acute gastroenteritis or children who presented with sporadic gastroenteritis. The real-time LC RT-PCR assay detected norovirus strains from three genogroup I (G-I) clusters (G-I/1, G-I/2, and G-I/3) and 10 genogroup II (G-II) clusters (G-II/1, G-II/2, G-II/3, G-II/4, G-II/6, G-II/7, G-II/10, G-II/12, G-II/15, and G-II/16). There was 100% concordance with the results from 58 stool specimens which tested positive by conventional RT-PCR assays. By dilution analysis, the real-time LC RT-PCR was 10,000 times more sensitive than the conventional RT-PCR. The new assay increased the number of samples in which noroviruses were detected by 19%. The real-time LC RT-PCR had a wide dynamic range, detecting from 5 to 5 × 10(6) copies of RNA per reaction, resulting in a theoretical lower limit of detection of 25,000 copies of RNA per g of stool. No cross-reactions were found with specimens containing sapovirus, rotavirus, astrovirus, and adenovirus. Because of the high sensitivity and specificity of the assay with a relatively rapid and simple procedure, the real-time LC RT-PCR will be useful as a routine assay for the clinical diagnosis of norovirus infection.